The body interior in anorexia nervosa: from interoception to conceptual representation of body interior - Paquet, Aude; Girard, Murielle; Passerieux, Céline; Boule, Marie-Christine; Lacroix, Aurélie; Sazerat, Pierre; Olliac, Bertrand; Nubukpo, Philippe (Frontiers in Psychology, 2024)
Background: Body image disorders are well documented in anorexia nervosa (AN); however, knowledge of interoceptive awareness (IA) in this population remains poor. This descriptive study investigated whether and how the representation of the interior of the body may have an impact on IA.The representations and knowledge of the inside of the bodybody interior were evaluated with a drawing task in 34 women with AN and 34 healthy controls (HCs). A lexicometric analysis was performed on the vocabulary used to describe the drawn body parts in a structured interview. It was assumed that the conceptual representation of the body interior inside of the body could be affected by or influence IA. Thus, the relationship between IA, measured with a the heartbeat task and the ischemia-induction test, and the drawings was explored. Other scales, such as those of body shape, awareness or satisfaction, were used to assess affective representations of the body.The drawing, lexicometric and IA results were similar in the two groups. No correlations were found among IA, body representation scores and inside of the body representation level of body interior. Only the representation of bones by the AN group was significantly different.Discussion: Increased visual attention to the skeleton or greater awareness of bone health could explain the stronger representation of bones in the AN group. The psychophysical therapy received by some AN participants (73%) did not seem to have influenced IA. Our results do not support a relationship between IA and the representation of the body interiorinside of the body.The study was registered in the Clinical Trials Registry (NCT03988218, registration 2019-03-25).